Domestic Violence Exposure Impact on Pediatric Mental Health Outcomes - Kanak , Neeraj (Journal of Educational Research and Policies, 2026)
This study explores the impact of Domestic violence (DV) on children’s mental health and well - being and investigating the psychological, behavioral, and emotional effects. Deliberate existing literature and qualitative insights, the research identifies the key challenges such as anxiety, depression, and post - traumatic stress disorder (PTSD) that children exposed to DV face. Factors like age, gender, and the availability of supportive networks are analyzed to understand their role in moderating or worsening these outcomes. The paper concludes with recommendations for interventions involving school, and caregivers to promote resilience and improve outcomes for children affected by DV.